Al3+ coordinated chitosan hydrogel with ultrahigh water absorbency and environmental response. (February 2022) - Zhang, Ze; Wang, Xiaodong; Liu, Ting; Liu, Lin; Yu, Chenglong; Tian, Yulin; Zhang, Xiaoxue; Shen, Jun
Graphical abstract: Highlights: Chitosan hydrogel with outstanding water storage capacity was prepared via Al 3+ coordination. The relation between synthesis parameters, chemical structure and properties of chitosan hydrogel was elucidated. The chitosan hydrogel exhibits response to external stimuli such as temperature, salinity and pH. Abstract: To fully utilize water, there is a great demand to develop eco-friendly materials with both ultra-high water absorbency and environmental response. In this study, the Al 3+ coordinated chitosan (CIS-Al 3+ ) hydrogels were prepared by formation of coordination bonds between Al 3+ and the skeleton of CIS hydrogels. AlCl3 was used to provide coordination center, and the formaldehyde aqueous solution was chosen as crosslinker. The effect of Al 3+ content and mass fraction of formaldehyde on gel formation, mechanical property and water storage capacity of CIS-Al 3+ hydrogels was investigated deeply. The obtained CIS-Al 3+ hydrogel can store more than 500% of its own weight of water without cracking, which demonstrates its super-absorbency. Besides, the CIS-Al 3+ hydrogels can swell/shrink in response to the change of external stimuli such as temperature, pH and salinity. These outstanding properties, together with the low-cost raw materials, simple preparation method and biocompatible and biodegradable properties, enable CIS-Al 3+ hydrogels to be applied as water storage materials in the agriculture field and pH-responsive materials in the future.